(untitled) (Journal of Engineering, 2020)
Mandali Dam is one of the small dams in Iraq; it is located on Haran Wadi, Gangir, just 3km north-east Mandali City. Mandali dam consists of four main parts, the dam body, the intake structure, the spillway, and the bottom outlet. The dam body is zoned earth filled with a central core. The main purposes of the dam are to maintain flow of Wadi Haran, supplying irrigation and drinking water to Mandali City, and recharging the groundwater. Over a period of seven years of operation, the dam lost its ability to store water due to accumulated sediments within its reservoir. The accumulated sediment is about 2.25million m3. The average annual rate of reduction during this period is about 0.321million m3. This is form an annual reduction in the original capacity of the dam by 14.26%. This paper attempts to study the hydraulic characteristics and the characteristics of sediment process including the velocity patterns, the distribution concentration, and bed change of sediment within the reservoir of Mandali Dam. The main conclusions of the study that, the velocity is very high in the upstream of the reservoir, due to the relatively narrow section of the wadi and high elevations of the bottom reservoir at this part and the velocities tend to decrease gradually toward the middle part of the reservoir. High concentration in the reservoir is located at the upstream of the reservoir, due to high flow velocities at the upstream and decrease gradually toward the reservoir outlet from spillway. The thickness of deposited sediment is very high in the middle part of the reservoir due to immediate drop in the velocity of water at this part lead to high deposition of sediment.